(3QSGdI GdJMPjQ hGdJfHjgs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe GdCRdi GdbOje hGdehdi GdcQje hGdQH GdQMje GdhGMO GdefRg Yf UaI GdCMGO GdaQO GdPi dGjTcd GdCaQGO s
(3BNQgG (B:s
(3hSOb eG ChYO Hg Zdg GdNdb hGYJeO ai Ojfg Ydi GdJhMjO hGdSOb hGdMeO dehdGfG hHg fSJYjf hgh MSHi hfYe GdfUjQ GdeYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B34s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds